University genres in disciplinary domains: social sciences and humanities and basic sciences and engineering Gêneros acadêmicos nas diferentes disciplinas: ciências sociais e humanidades e ciências básicas e engenharia - Giovanni Parodi (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada, 2009)
The issue of disciplinarity is becoming increasingly salient in discourse studies. Questions of how differences in the structures of intellectual fields and curricula help shape educational experiences and outcomes are the focus of studies across a variety of disciplines using a range of approaches. One way to access the specialized written genres employed by academia is to begin from the tenet that all materials read by students during their university training reveal relevant data about disciplinary genres. This article presents research that focuses on the collection, construction, and description of an academic corpus based on texts collected in four disciplinary domains of knowledge: Industrial Chemistry, Construction Engineering, Social Work, and Psychology. A review of the concepts of genre and academic discourse is presented. This is followed by a description of the procedures of collecting and organizing the Academic Corpus PUCV-2006, which comprises almost 60 million words. In addition, a preliminary genre typology of the 491 text corpus is provided. O tema da disciplinaridade está se tornando cada vez mais relevante nos estudos do discurso. Uma maneira de conhecer os gêneros escritos específicos utilizados na universidade, é ter acesso ao material que os estudantes lêem durante sua formação universitária. Este artigo apresenta uma investigação que tem como foco a coleta, construção e descrição de um corpus acadêmico baseado em textos de quatro áreas: Química Industrial, Engenharia da Civil, Serviço Social e Psicologia. Apresenta-se uma revisão dos conceitos e gêneros do discurso acadêmico. Segue-se uma descrição dos procedimentos de coleta e organização do corpus acadêmico PUCV-2006, que compreende um total de 60 milhões de palavras e uma tipologia dos gêneros a partir dos 491 textos do corpus.